MEMICU HASIL BELAJAR SAINS SISWA SMP MELALUI PEMBELAJARAN KONTEKSTUAL - Ni Nyoman Parmithi (Program Studi Pendidikan Biologi Universitas PGRI Mahadewa Indonesia, 2024)
This study aims to improve the science learning outcomes of grade VIII students of SMP Negeri 1 Sukawati, Gianyar through contextual learning. By involving a sample of 69 people taken by simple random sampling, but what is randomized is the class because it cannot change the classes that have been formed previously. Thus, this study is classified as a quasi-experiment with a pretest-posttest control group design. The instrument used to collect data is a multiple-choice science learning outcome test that has been tested for validity and reliability coefficient. The data collected has been tested for its prerequisites and is in a normal distribution and has a homogeneous variance so that the hypothesis test with the t-test can be carried out. From the results of the hypothesis test, it was found that the science learning outcomes of students who took contextual learning were better than the science learning outcomes of students who took conventional learning. For that, in order to obtain more optimal science learning outcomes, it is recommended to use contextual learning.